THE EFFECT OF PAY SATISFACTION AND SATISFACTION WITH SUPERVISOR ON TURNOVER INTENTION MEDIATED BY WORK MOTIVATION - Ulfa Ulfa; Zakhyadi Ariffin (Adisam Publisher, 2026)
Ulfa, The Effect of Pay Satisfaction and Satisfaction With Supervisor on Turnover Intention is mediated by Work Motivation (Study at PT. Kalimantan Prima Persada Rantau), Zakhyadi Ariffin (Supervisor). This research aims to determine and analyze the influence of pay satisfaction on turnover intention, satisfaction with supervisor on turnover intention, work motivation on turnover intention, the mediating role of work motivation on pay satisfaction on turnover intention, and the mediating role of work motivation on satisfaction with supervisor on Turnover intention in PT studies. Kalimantan Prima Persada Rantau. This research uses a quantitative type of research. The research method uses a questionnaire with a total of 128 samples as respondents. Variable measurement uses an interval scale, specifically a Likert scale with a scale weight of 1 (strongly disagree) to 5 (strongly agree). Moreover, data analysis in this research uses Structural Equation Modeling Partial Least Squares (PLS) with the help of SmartPLS software. The results of this study are concluded as follows: (1) there is a negative influence of pay satisfaction on turnover intention, (2) there is a negative influence of satisfaction with supervisor on turnover intention, (3) there is a negative influence of work motivation on turnover intention, (4) there is a positive influence of pay satisfaction on work motivation, (5) there is a positive influence of satisfaction with supervisor on work motivation, (6) there is an influence of work motivation mediating the relationship between pay satisfaction and turnover intention, and finally, (7) there is an influence of work motivation mediating the relationship of satisfaction with supervisors on turnover intention.